A great reckoning - Penny, Louise (New York : Minotaur Books, 2016)
When an intricate old map is found stuffed into the walls of the bistro in Three Pines, it at first seems no more than a curiosity. But the closer the villagers look, the stranger it becomes. Given to Armand Gamache as a gift the first day of his new job, the map eventually leads him to shattering secrets--to an old friend and older adversary.
Keywords: Gamache, Armand (Fictitious character) -- Fiction; Police -- Qub̌ec (Province) -- Fiction; Murder -- Investigation -- Fiction; Detective and mystery fiction; Mystery fiction